The microbiologic profile of diabetic foot infections in Turkey: a 20-year systematic review: Diabetic foot infections in Turkey - Hatipoglu, M.; Mutluoglu, M.; Uzun, G.; Karabacak, E.; Turhan, V.; Lipsky, B. A. (European journal of clinical microbiology & infectious diseases, 2014)
The causative pathogens in diabetic foot infections differ in studies of European compared with Asian populations. The purpose of this study was to determine the causative microorganisms and their antibiotic sensitivity patterns in diabetic patients with a foot infection in Turkey, a country at the crossroads of these two continents. We performed a comprehensive literature search to identify all published studies pertaining to DFIs in patients cared for in Turkey. To assess changes in causative organisms and their antibiotic sensitivity patterns over time, we compared the results of just the most recent 5 years (2007–2011) with those of the past 20-years (1989–2011). We identified 31 studies meeting our inclusion criteria. Overall, these studies reported 2,097 patients, from whom 1,974 microorganisms were isolated. The total percentage of gram-negative and gram-positive aerobic bacteria were similar in each of the assessed periods. The rate of isolation of Staphylococcus aureus during the entire period, compared with just the past 5 years, was 23.8 % and 19.1 %, respectively, while the rate of methicillin-resistant S. aureus was 7.8 % and 5.7 %, respectively. The isolation rate of Pseudomonas aeruginosa was 13.7 % for the entire period and 14.9 % for the past 5 years. While linezolid, vancomycin and teicoplanin were the most active agents against gram-positive microorganisms, imipenem and cefoperazone-sulbactam were the most active against gram-negative microorganisms. This systematic review demonstrated few substantial changes in diabetic foot microbiology over the past 20 years. The data may help develop and update local clinical guidelines regarding antibiotic therapy for diabetic foot infections in Turkey. Further studies, especially with optimal culture methods, would be useful to validate these findings.